Dampak Alokasi Dana Desa pada Pemberdayaan Masyarakat dalam Peningkatan Kesejahteraan Masyarakat: Survey pada Desa Dumati Kecamatan Telaga Biru Kabupaten Gorontalo - Stevie Gibernau Paendong,; Rio Monoarfa,; Siti Pratiwi Husain, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out the impact of the location of village funds on community empowerment in improving community welfare. This research uses qualitative research methods, the data sources used are primary and secondary data where this research uses interview data collection techniques and more in-depth documentation in Dumati Village, Telaga Biru District, Gorontalo Regency. The research results show that the Village Fund Allocation allocated from the government has been maximized and is starting to have a good impact on empowering the Dumati Village community. Which is measured through indicators in utilizing village potential, as well as the ability to manage Village Fund Allocations in the field of community empowerment. In terms of utilizing the village's potential, it has been done well, namely by providing food plant seeds in the form of vegetable seeds, namely tree seeds and fertilizer for animal products, namely chicken seeds, to farmers and breeders, with the aim of later being able to advance the economy in the village. In terms of utilizing capabilities, the village government has also carried out empowerment in the BUMDES sector with the aim of helping the community to improve the welfare of the village community. However, what is lacking in the Dumati Village government is that its ability to manage is not optimal in utilizing the very strategic conditions of the village.